2018
DOI: 10.1515/aoas-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and Meat Quality of Male and Female Water Buffaloes Finished Under an Intensive Production System

Abstract: Carcass and meat quality of male and female Anatolian Water Buffalos were investigated using 10 carcasses from each gender. Gender had no influence on carcass characteristics, except warm carcass weight, which was 13% higher in males compared to females. Meat from male water buffalos had higher ultimate pH and lightness (L*), but lower redness (a*) values than females. Meat samples aged for 21-day had lower values for expressed juice, cooking loss and Warner Bratzler shear force compared with those of 7-day ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
(43 reference statements)
2
12
1
1
Order By: Relevance
“…WBsSF values observed in this experiment are below those reported in the literature for not aged meats of water buffaloes with 24-36 months older (Spanghero, et al, 2004;Ekiz, et al, 2018;Li, et al, 2018;Mello, et al, 2018). This greater tenderness 72 h postmortem can be attributed to the chilling process adopted and the consequent greater proteolysis.…”
Section: Resultscontrasting
confidence: 72%
“…WBsSF values observed in this experiment are below those reported in the literature for not aged meats of water buffaloes with 24-36 months older (Spanghero, et al, 2004;Ekiz, et al, 2018;Li, et al, 2018;Mello, et al, 2018). This greater tenderness 72 h postmortem can be attributed to the chilling process adopted and the consequent greater proteolysis.…”
Section: Resultscontrasting
confidence: 72%
“…In the older animals, the PUFA/SFA ratio was higher in bulls relative to steers, combined with a lower atherogenic index, suggesting that meat from intact males has nutritional advantages with respect to steer meat. The meat from males also showed a better FA profile compared to females, thanks to its higher n-3 content, with a consequent lower n-6/n-3 ratio [88]. A study on the impact of buffalo meat consumption on cardiovascular risk revealed possible associations with several beneficial effects, including lower levels of total cholesterol and more favourable vascular parameters [96].…”
Section: Chemical Composition and Nutritional Propertiesmentioning
confidence: 99%
“…The large variability in the age of the animals used in the different studies, together with the differences in the age range within studies, might explain the conflicting results. Sex also seems to affect pH, with higher values reported for males [88,118]. No effects of the diet on pH were reported [33,50].…”
Section: Trait Rangementioning
confidence: 99%
See 2 more Smart Citations